Screening for Eustachian Tube Dysfunction in Clinical Practice Using the Eustachian Tube Dysfunction Questionnaire‐7. (3rd January 2022) - Commesso, Emily A.; Kaylie, David; Risoli, Thomas; Peskoe, Sarah B.; Witsell, David; Coles, Theresa
Abstract : Objectives/Hypothesis: To evaluate the ability of the Eustachian Tube Dysfunction Questionnaire‐7 (ETDQ‐7) to discriminate between patients with Eustachian tube dysfunction (ETD) and Non‐ETD diagnoses, and identify symptom information to improve ability to discriminate these groups. Study Design: Cohort study. Methods: Pilot retrospective study with consecutive adult patients presenting to otology clinics and one general otolaryngology clinic in an academic health system. Patients were administered ETDQ‐7 with eight additional symptom items. Electronic health records were reviewed for demographic and diagnostic information. Patients were grouped into diagnosis categories: 1) True ETD, 2) experiencing ear fullness (EF) not due to ETD, and 3) Control patients without ETD‐related disorders or EF. ETDQ‐7 and symptom item scores were compared by the diagnosis group. Receiver‐operative characteristics curves and area under the curve (AUC) were generated for each ETD diagnosis group based on ETDQ‐7 and symptom scores. Results: Of the 108 patients included in this study 74 (68.5%) were diagnosed with ETD. Patients with ETD had higher (indicating worse symptom burden) overall ETDQ‐7 scores than Control group (Median [Q1, Q3] 3.0, [1.7, 4.1]; versus 1.5 [1.0, 3.4] P  = .008). There was no statistically significant difference between overall ETDQ‐7 scores for ETD and Non‐ETD EF patients ( P  = .389). The AUC for the ETDQ‐7 in discriminating ETD from other conditions that cause EF was 0.569; the addition of 8 symptom questions to the ETDQ‐7 improved AUC to 0.801. Conclusion: Additional patient‐reported symptom information may improve the ability to discriminate ETD from other similarly presenting diagnoses when using ETDQ‐7. Level of Evidence: 3 Laryngoscope, 132:2217–2223, 2022